2011
DOI: 10.1038/pj.2011.14
|View full text |Cite
|
Sign up to set email alerts
|

High-performance hybrid materials prepared by the thermo-reversible Diels–Alder polymerization of furfuryl ester-terminated butylene succinate oligomers and maleimide compounds

Abstract: A furfuryl ester-terminated butylene succinate oligomer (FBSO) with M n 1800 and M w 2800 was synthesized by the condensation of furfuryl alcohol with a carboxyl-terminated butylene succinate oligomer. The reaction of FBSO and 1,1¢-(methylenedi-4,1-phenylene)bismaleimide (BMI) in chloroform at 60 1C for 48 h yielded an exo-rich Diels-Alder (DA) adduct ((P(FBSO-BMI)) with M n 9000 and M w 15 500. The gel permeation chromatography analysis of the products of heating a reaction mixture of P(FBSO-BMI) in dimethylf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…For example, a furfuryl ester-terminated butylene succinate oligomer with a M n of 1,800 was synthesized by the condensation of furfuryl alcohol with a carboxyl-terminated butylene succinate oligomer. 73 This polymer was used for condensation by the Diels-Alder reaction. Also, the two carboxylic acid groups of PBS were modified for azide to use a click reaction with hydrophilic polyacrylic acid derivatives.…”
Section: Pbsmentioning
confidence: 99%
“…For example, a furfuryl ester-terminated butylene succinate oligomer with a M n of 1,800 was synthesized by the condensation of furfuryl alcohol with a carboxyl-terminated butylene succinate oligomer. 73 This polymer was used for condensation by the Diels-Alder reaction. Also, the two carboxylic acid groups of PBS were modified for azide to use a click reaction with hydrophilic polyacrylic acid derivatives.…”
Section: Pbsmentioning
confidence: 99%
“…The same peak (υCH=CH) appeared in the spectrum of cross-linked grafted imidazole products (IMG1) at 1510 cm −1 ( Figure 2 b), overlapping with the peak of imidazole ring stretching (υ imidazole ring) [ 40 , 44 ]. As can be seen in Figure 2 b, an additional peak at 702 cm −1 which is assigned to =CH out of plane bending vibration of the maleimide ring (γ = CH), appears in the spectra of IMG1 [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that a specific proportion of the raw materials took part in cross-linking reactions. Cross-link density was calculated using the formula E' = 3nRT (where E' is the storage modulus at the rubbery region, n is the cross-linking density, R is the universal gas constant and T is absolute temperature in K (T = Tg + 25 °C)) [10,27]. Figure 7 displays the DMA analysis of the film samples which demonstrates the variation of the storage and loss modulus with temperature.…”
Section: Resultsmentioning
confidence: 99%